Nilai Pendidikan Karakter dalam Cerpen Numbrag - Apriani, Ni Wayan (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2023)
This study aims to describe the formal structure, narrative structure and character education values in the Numbrag short story. The methods used are formal methods and qualitative methods. The type of data used in this study is qualitative data because this research is oriented towards a description of the formal and narrative structures as well as the value of character education in the short story Numbrag. Primary data in this study were obtained directly from the text of the Numbrag short story while secondary data were obtained from relevant sources such as scientific journals and reference books. Data collection uses the document recording method. After the data is collected, then the data is processed using non-statistical analysis or descriptive data processing using induction and argumentation techniques. From the results of research and discussion it can be seen that the formal structure that builds the Numbrag short story consists of a variety of languages and language styles. The variety of languages used include alus, medium, andap and rough bases. While the style of language used is the type of sesawangan. The narrative structure consists of a synopsis, theme, character, characterization, plot, setting and message. There are three character education values contained in the Numbrag Short Story, namely discipline, social care and fond of reading.